2007
DOI: 10.1063/1.2786592
|View full text |Cite
|
Sign up to set email alerts
|

Changing and reversing the exchange bias in a current-in-plane spin valve by means of an electric current

Abstract: Current driven magnetization reversal in microstructured spin valve with current-in-plane configuration J. Appl. Phys. 105, 07D118 (2009); 10.1063/1.3068483Effect of polarized current on the exchange bias in a current-in-plane spin valve Exchange-biasing asymmetric spin valves using a pulsed current

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 15 publications
3
48
0
Order By: Relevance
“…However, because of scattering processes, conduction electron flow is not confined to specific layers of the EBSV structure, but can move from layer to layer, thereby transferring spin angular momentum between the layers. In a series of papers, Tang et al [30][31][32][33][34][35] reported on the effects of high CIP currents on the exchange bias in room-temperature experiments. They used a standard four-probe method to measure CIP-MR of sputtered EBSV of the form F/N/F/AFM with free F = 10-12 nm of NiFe, N = 4 nm of Cu, pinned F = 3-12 nm of NiFe and AFM = 15 nm of FeMn.…”
Section: Initial Experiments: Antiferromagnetic Spin-transfer Torque-mentioning
confidence: 99%
“…However, because of scattering processes, conduction electron flow is not confined to specific layers of the EBSV structure, but can move from layer to layer, thereby transferring spin angular momentum between the layers. In a series of papers, Tang et al [30][31][32][33][34][35] reported on the effects of high CIP currents on the exchange bias in room-temperature experiments. They used a standard four-probe method to measure CIP-MR of sputtered EBSV of the form F/N/F/AFM with free F = 10-12 nm of NiFe, N = 4 nm of Cu, pinned F = 3-12 nm of NiFe and AFM = 15 nm of FeMn.…”
Section: Initial Experiments: Antiferromagnetic Spin-transfer Torque-mentioning
confidence: 99%
“…Furthermore, nonuniform current flows inherent to the point-contact technique (Wei et al, 2007) give only a qualitative picture. In addition experiments are sometimes perturbed by unstable antiferromagnetic configurations (Urazhdin and Anthony, 2007) or reconfiguration originating from Joule heating and not spin-transfer torque (Tang et al, 2007(Tang et al, , 2010Dai et al, 2008). New experimental geometries and stacks symmetries need to be proposed to obtain quantitative data.…”
Section: Seeking Spin-transfer Torque Experimentallymentioning
confidence: 99%
“…It has been predicted theoretically that spin-transfer torque (STT) can act on AFM, causing reorientation of its spin configuration, domain wall motion and stable oscillation or precession of the Neel vector [18][19][20][21] . Several follow-up experiments on exchange-biased spin-valves [22][23][24][25] have shown that current induced STT is able to affect the exchange bias at the FM/AFM interface, indirectly suggesting the presence of STT effect in AFM. More recently, spin pumping and spin torque ferromagnetic resonance (ST-FMR) measurements on FM/AFM/HM trilayers demonstrated that spin-current can travel across both NiO and IrMn at a reasonably large distance and high efficiency [26][27][28][29][30] .…”
Section: Introductionmentioning
confidence: 99%